2008 International Conference on High Performance Switching and Routing 2008
DOI: 10.1109/hspr.2008.4734458
|View full text |Cite
|
Sign up to set email alerts
|

Trading network management complexity for blocking probability when placing optical regenerators

Abstract: Optical signal regenerators (3R) are required to overcome the adverse effect of fiber and other transmission impairments. 3R units may be placed either at every node (full placement) or at some selected nodes (sparse placement) of the optical network. It has been argued [1] that while the latter placement strategy may not be optimal in terms of the total number of 3R units required to support a given set of static traffic demands, it offers a number of practical advantages over the former, e.g., a contained … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…This approach removes the possibility of an invalid path that could be produced by the procedure in [47]. In [48], it was shown that the blocking probability of the sparse regenerator placemen is comparable to that of an opaque network. The paper also compares the RPP strategies in [6,49].…”
Section: Algorithms For Rpp In Network Handling Ad-hoc Lightpath Demmentioning
confidence: 99%
“…This approach removes the possibility of an invalid path that could be produced by the procedure in [47]. In [48], it was shown that the blocking probability of the sparse regenerator placemen is comparable to that of an opaque network. The paper also compares the RPP strategies in [6,49].…”
Section: Algorithms For Rpp In Network Handling Ad-hoc Lightpath Demmentioning
confidence: 99%
“…Various European projects (i.e., DICONET [11], PHOSPHO-RUS [12], NOBEL [13]) dealt with translucent dimensioning. In other works [9,14,15] a particular emphasis is given on where to deploy regenerators to minimize the number of rejected connections in a dynamic scenario.…”
Section: Prior Workmentioning
confidence: 99%
“…In [9,14] the connectivity graph (see a formal definition in Section IV) has been proposed to solve RPP alone, and in [16] it is applied jointly with traffic grooming. Effective heuristic methods have been described in [20], though they still do not optimize the number of TXPs and fibers, but only the number of regeneration sites.…”
Section: Prior Workmentioning
confidence: 99%